2021
DOI: 10.1016/j.ultsonch.2021.105652
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted covalent reaction of myofibrillar protein: The improvement of functional properties and its potential mechanism

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 76 publications
2
34
0
Order By: Relevance
“…This suggested an enhanced reaction surface for improving enzyme-protein interactions for structural unfolding during hydrolysis [24] , [53] . The results were in agreement with the findings of microstructure analysis, and similar effects were reported for chicken breast myofibrillar proteins, attributed to the opening of the protein chains by ultrasound to induce 3-dimensional structural modification for increasing SSA [21] . Previous studies have reported reductions in particle size of king prawn tropomyosin, golden threadfin bream hydrolysates and small yellow croaker myofibrillar proteins from cold plasma and ultrasound treatments [5] , [49] , [52] .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This suggested an enhanced reaction surface for improving enzyme-protein interactions for structural unfolding during hydrolysis [24] , [53] . The results were in agreement with the findings of microstructure analysis, and similar effects were reported for chicken breast myofibrillar proteins, attributed to the opening of the protein chains by ultrasound to induce 3-dimensional structural modification for increasing SSA [21] . Previous studies have reported reductions in particle size of king prawn tropomyosin, golden threadfin bream hydrolysates and small yellow croaker myofibrillar proteins from cold plasma and ultrasound treatments [5] , [49] , [52] .…”
Section: Resultssupporting
confidence: 91%
“…4 a). Treatments increased the SSA and decreased the D 43 , suggesting enhanced adsorption capacity and the promotion of electrostatic repulsion, respectively [21] . The SSA increased to 0.589, 0.649 and 0.437 m 2 /g after individual treatments and 0.644, 0.910 and 0.502 m 2 /g after combination treatments, from DWS values of 0.502, 0.592 and 0.326 m 2 /g, respectively for CAH, CCH and CPH.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It can promote the opening of hydrophobic region inside protein, thus promoting the further binding capacity of protein and polyphenols [6] . In addition, ultrasound can have cavitation and shear effect on the structure and functional properties of protein, so as to assist the improvement of food properties [7] . Some scholars found that the ultrasound protein used in bread production can effectively improve the nutritional quality of bread [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the thawing methods, the air thawing increased the exposure to ROS due to oxidative conditions maximally. On the contrary, the ultrasonic cavitation and saline of UST treatment increased thawing rate and shortened the thawing time, which protected the muscle damage from protein oxidation [41] The increase in carbonyl may lead to the crosslinks of protein and influence the protein structure, which reduced the muscle water holding capacity [42] . The results corresponded to the changes in the WHC of fish under different thawing methods ( Fig.…”
Section: Results and Analysismentioning
confidence: 99%